Effectiveness of the Application of the Team Assisted Individualization Model to Improve the Learning Independence of Senior High School Students in Optical Instrument Material - Tika Elviana; Muhammad Nasir; Mitri Irianti (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2020)
This research aimed to determine the differences in the improvement of students' physics learning independence through the application of the Team Assisted Individualization (TAI) learning model. This type of research used a quasi-experimental design with a non-equivalent control group design. The research sample was determined from the population of class XI IPA students of SMAN 1 Pekanbaru, based on the results of the normality and homogeneity tests of the population. Classes that were declared normal and homogeneous, two classes were randomly selected as the control class (36 students) and the experimental class (36 students). The data collection instrument used a student learning independence questionnaire for pre-test and post-test. Data were analyzed using descriptive and inferential analysis. The results of the descriptive analysis obtained the independent learning average of the experimental class was 2.71 with the high category and the control class 2.47 with the low category. The results of the inferential analysis show that there are significant differences in student learning independence before and after learning by applying the TAI learning model. Therefore, the use of the TAI learning model can improve the learning independence of class XI IPA students of SMAN 1 Pekanbaru on the material of optical instruments.